Genetic diversity and expression analyses of secreted in xylem effector genes of Fusarium oxysporum f. sp. cubense isolated from Peninsular Malaysia - Ahmad, Suhanna (2021)
Banana is a commercially important fruit in the majority of tropical and subtropical countries. Banana plantations cover nearly 35,000 hectares of land, accounting for approximately 24% of Malaysia's total fruit production, with Johor plantations accounting for approximately 32% of the nation's banana production. The Fusarium wilt pathogen, Fusarium oxysporum f. sp. cubense (Foc) is a major cause of disease in the banana industry, limiting banana production in Malaysia and causing significant economic losses. Currently, the majority of locally grown bananas (Berangan, Rasthali, Mas) and plantains used for cooking or processing (Raja, Abu, and Awak) have been found to be susceptible to Foc-TR4. To date, AFLP, RAPD, ISSR and SSR markers are extensively used in PCR-based molecular characterization of Foc. Although these markers are effective in characterizing Foc, they all have their own limitations. An effector gene known as Secreted in Xylem (SIX) has been explored to broaden the molecular diagnostic toolbox for Foc. The main objective of this study was to identify expression of SIX genes in banana plantlet during infection with the Foc-TR4. This will be an important step in understanding the pathogenicity response of the plant and will help to develop any disease management strategies. In this study, the virulence potential of 27 isolates of Foc of banana based on pathogenicity test and the presence of SIX1, SIX7 and SIX8 genes were determined. All of 27 Foc ‘Tropical Race 4’ (TR4) (VCG 01213/160) isolates were obtained from Biological Control Laboratory, Department of Plant Protection, University Putra Malaysia (UPM). All isolates were pathogenic towards Musa acuminata Berangan AAA at different severity levels under greenhouse condition. Pathogenicity assays indicated that the level of aggressiveness varies between isolates. The Foc-TR4 isolates were screened for the presence of three SIX genes (SIX1, SIX7 and SIX8) and the genetic differentiation of Foc- TR4 was evaluated by PCR analysis using three specific primers (SIX1, SIX7 and SIX8). Among these three SIX genes, SIX1 and SIX8 genes were detected in all 27 Foc-TR4 isolates from Peninsular Malaysia. The presence of SIX1 and SIX8 in Foc-TR4 suggested these genes were likely involved in pathogenicity on banana. Phylogenetic analysis using SIX1 and SIX8 sequences showed that they were related to TR4 isolates (VCG 01213/16) from Australia and Indonesian with bootstrap values of 94% and 100%, respectively. There was no variation observed in the SIX1 and SIX8 sequences since all 27 isolates clustered in the same clade. Virulence level do not correlate with the existence or lack of these genes. Highest and lowest disease severity values (80.73% and 10.42%) on banana plantlet were selected. The T30 and T36 isolates were found to be highly aggressive and weakly aggressive, respectively. Both T30 and T36 isolates were analyzed by qRT-PCR analyses for the expression of SIX1 and SIX8 genes to elucidate whether these genes play a role in the pathogenicity response of Foc-TR4 on Musa acuminate cv. Berangan plantlets during early and late of infection stages. Expression analyses of SIX1 and SIX8 were constructed from banana roots collected after 0, 2, 4, 8, 12, 15, 20- and 30-day post-infection (dpi). The SIX1 and SIX8 genes were expressed after being induced by the host and showed higher expression at 8 dpi and 12 dpi respectively in both T30 and T36 isolates. From these results, it can be concluded that highly expressed virulence-associated genes, SIX1 and SIX8 can be used as markers for the assessment of Foc-TR4 virulence.